The study of neutrophil to lymphocyte ratio as a predictor of treatment response and mortality in sepsis and septic shock patients in the intensive care unit - الرحال, الياس; فراس حسين; محمد الخير (Latakia University Journal -Medical Sciences Series, 2024)
Background: Neutroplil to lymphocyte ratio (NLR) is an easy marker to have from the blood sample (CBC) and it can be used as a predictor of mortality for patients in intensive care unit (ICU). Aim: The aim of this study is to assess the efficacy of the neutrophil lymphocyte ratio (NLR) as a predictor of mortality in patients with sepsis and septic shock in intensive care unit (ICU). Materials and methods: A prospective cohort study was conducted in patients who consulted Tishreen University Hospital in Lattakia for severe sepsis and septic shock in intensive care unit between August 2022- August 2023. NLR was calculated from complete blood count in the first and third day of admission in intensive care unit, the sensitivity of NLR was compared between the two days, and the prognosis of mortality during 28 days of the ICU admission was studied. . The sensitivity and specificity were also compared between the NLR and CRP indicators on the third day. Results: A total of 104 patients with a mean age of 62.11 years were included. 25% of patients had septic shock and 75% were died. NLR was calculated in the first and third day of admission ,and the patients were divided according to NLR values into 3 groups the first (0.1-2.5) the second (0.6-10) the third (>10). In total of 104 (male 40.4%) the nonsurvivors with shock were 100% and 52.7% nonsurvivors without shock, 0% survivors with shock and 33.3% survivors without shock. In the first day, there was no association between the NLR groups and mortality, while in the third day, (82.1%) were nonsurvivors and 7.7% were survivors in the third group while, in the second group 17.9% were nonsurvivors and 84.6% were survivors. In the third day if the NLR> 9.05 the mortality odds ratio was CI 4.8[1.5-11.2] with P-value 0.0001 . Conclusion: The NLR can predict mortality in ICU patients with sepsis and septic shock. If the NLR is >9.05 on the 3rd day of admission, the risk of mortality is high and it is more sensitive than the first day and it is more sensitive and specific than CRP on the third day.